JERGILIKLI ILIMPAZLARDÍŃ QARAQALPAQ DIALEKTOLOGIYASÍ TARAWÍNDAǴÍ MIYNETLERI - Shınnazarova, Saodat Jubatqanovna; Kaypnazarova, Miyrixan Kalmuratovna (SCIENCE and SOCIETY, 2026)
This article examines the works of local scholars and their unique contributions to the development of Karakalpak dialectology. The research results prove that Karakalpak dialectology has been fully formed both theoretically and practically.